Pulmonary Artery Size in Interstitial Lung Disease and Pulmonary Hypertension: Association with Interstitial Lung Disease Severity and Diagnostic Utility - Chin, Matthew; Johns, Christopher; Currie, Benjamin J.; Weatherley, Nicholas; Hill, Catherine; Elliot, Charlie; Rajaram, Smitha; Wild, Jim M.; Condliffe, Robin; Bianchi, Stephen; Kiely, David G.; Swift, Andrew J. (Frontiers in Cardiovascular Medicine, 2018)
Purpose It is postulated that ILD causes PA dilatation independent of the presence of pulmonary hypertension (PH), so the use of PA size to screen for PH is not recommended. The aims of this study were to investigate the association of PA size with the presence and severity of ILD and to assess the diagnostic accuracy of PA size for detecting PH. Methods Incident patients referred to a tertiary PH centre underwent baseline thoracic computed tomography (CT), magnetic resonance imaging (MRI) and right heart catheterisation (RHC). Pulmonary artery diameter was measured on CT pulmonary angiography and pulmonary arterial areas on MRI. A thoracic radiologist scored the severity of ILD on CT from 0–4, 0=absent, 1=1–25%, 2=26–50%, 3=51–75%, and 4=76–100% extent of involvement. Receiver operating characteristic analysis and linear regression were employed to assess diagnostic accuracy and independent associations of PA size. Results 110 had suspected PH due to ILD (age 65 years (SD 13), M:F 37:73) and 379 had suspected PH without ILD (age 64 years (SD 13), M:F 161:218). CT derived main PA diameter was accurate for detection of PH in patients both with and without ILD - AUC 0.873, p=<0.001, and AUC 0.835, p=<0.001, respectively, as was MRI diastolic PA area, AUC 0.897, p=<0.001, and AUC 0.857, p=<0.001, respectively Significant correlations were identified between mean pulmonary arterial pressure (mPAP) and PA diameter in ILD (r = 0.608, P < 0.001), and non-ILD cohort (r = 0.426, P <0.001). PA size was independently associated with mPAP (p<0.001) and BSA (p=0.001), but not with Forced vital capacity % predicted (p=0.597), Transfer factor of the lungs for carbon monoxide (TLCO) % predicted (p=0.321) or the presence of ILD on CT (p=0.905). The severity of ILD was not associated with pulmonary artery dilatation (r = 0.071, p = 0.459). Conclusions Pulmonary arterial pressure elevation leads to pulmonary arterial dilation, which is not independently influenced by the presence or severity of ILD measured by FVC, TLCO, or disease severity on CT. Pulmonary arterial diameter has diagnostic value in patients with or without ILD and suspected PH.